2020
DOI: 10.1002/lipd.12249
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Genome Editing for Improving Seed Oil Content and Fatty Acid Composition in Oilseed Crops

Abstract: A continuous rise in demand for vegetable oils, which comprise mainly the storage lipid triacylglycerol, is fueling a surge in research efforts to increase seed oil content and improve fatty acid composition in oilseed crops. Progress in this area has been achieved using both conventional breeding and transgenic approaches to date. However, further advancements using traditional breeding methods will be complicated by the polyploid nature of many oilseed crops and associated time constraints, while public perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 168 publications
0
12
0
Order By: Relevance
“…This platform requires a Cas nuclease, which produces a double-stranded DNA break, and a single guide RNA (sgRNA), which includes a short user-defined sequence that guides the Cas nuclease to a highly specific chromosomal locus of choice immediately upstream of a protospacer-adjacent motif (PAM). Due to the unlinked nature of the resulting edit and the introduced transgene, this technology allows for the rapid production of non-transgenic germplasm bearing mutations that are identical in nature to those achieved spontaneously or through conventional breeding approaches such as chemical mutagenesis ( Subedi et al, 2020a , b ). While the regulatory status of crop varieties derived from genome editing is still uncertain in some countries, many others, including the United States, have concluded that in the absence of foreign DNA they are not “GM,” and will therefore not be subjected to costly and burdensome regulatory processes ( Schmidt et al, 2020 ; Singer et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…This platform requires a Cas nuclease, which produces a double-stranded DNA break, and a single guide RNA (sgRNA), which includes a short user-defined sequence that guides the Cas nuclease to a highly specific chromosomal locus of choice immediately upstream of a protospacer-adjacent motif (PAM). Due to the unlinked nature of the resulting edit and the introduced transgene, this technology allows for the rapid production of non-transgenic germplasm bearing mutations that are identical in nature to those achieved spontaneously or through conventional breeding approaches such as chemical mutagenesis ( Subedi et al, 2020a , b ). While the regulatory status of crop varieties derived from genome editing is still uncertain in some countries, many others, including the United States, have concluded that in the absence of foreign DNA they are not “GM,” and will therefore not be subjected to costly and burdensome regulatory processes ( Schmidt et al, 2020 ; Singer et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Modern precision breeding tools, including genome editing, present an opportunity for such targeted breeding approach. In addition, genome editing would be extremely useful in making pathway engineering needed to develop soybean varieties with enhanced protein and oil contents (Aili Bao, 2020;Subedi et al, 2020). CRISPR-Cas9 due to flexibility and ease of the design has become an important genome engineering tool for creating targeted DSBs required for precision breeding applications (Wiedenheft et al, 2011;Jinek et al, 2012;Cong et al, 2013;Xing et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The success of conventional plant breeding techniques has been extensively studied to regulate heat stress tolerance mechanisms in various crops including oilseeds, but these techniques are very time consuming and cumbersome. As an alternative, genome editing using clustered regularly interspaced short palindromic repeats/CRISPR-associated protein (CRISPR/Cas) has been raised as an innovative technique for precise and efficient genetic manipulations in plant genomes (Subedi et al, 2020 ). Although, there is a discrete lack of information regarding negative regulators within the heat stress response, and thus studies involving CRISPR/Cas-mediated enhancement of high-temperature stress tolerance mechanisms remain scarce.…”
Section: Mechanism Of Heat Stress Tolerance In Plantsmentioning
confidence: 99%